1981
DOI: 10.1159/000250168
|View full text |Cite
|
Sign up to set email alerts
|

Variably Acid-Fast Bacteria in a Case of Systemic Sarcoidosis and Hypodermitis Sclerodermiformis

Abstract: The histologic finding of variably acid-fast coccoid forms in all the available biopsy material (skin, lymph nodes, and lung) from a case of coexisting scleroderma-like cutaneous disease (hypodermitis sclerodermiformis) and systemic sarcoidosis is reported The morphologic size, shape, and staining characteristics of these microbes, along with the presence in the lung of ‘large bodies’, suggest that these microbes are cell wall deficient L forms of mycobacteria. Culture of the skin of the scleroderma-like lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…These include: histopathological appearances of the granulomas [2]; reports of mycobacterial disease either existing coincidentally, succeeding or pre-dating sarcoidosis [59,60]; and the finding of mycobacteria in occasional granulomas of sarcoidosis [61][62][63]. Passage experiments have also suggested that mycobacteria with characteristics of M. tuberculosis may be the incriminating agent [64][65][66][67].…”
Section: Trials Excludedmentioning
confidence: 99%
“…These include: histopathological appearances of the granulomas [2]; reports of mycobacterial disease either existing coincidentally, succeeding or pre-dating sarcoidosis [59,60]; and the finding of mycobacteria in occasional granulomas of sarcoidosis [61][62][63]. Passage experiments have also suggested that mycobacteria with characteristics of M. tuberculosis may be the incriminating agent [64][65][66][67].…”
Section: Trials Excludedmentioning
confidence: 99%
“…A mouse monoclonal antibody was developed against M tuberculosis H37RV whole cell antigen using the Kohler-Milstein technique.27 One gram of wet cell pellet of bacteria was suspended in 10 USA). Plates with cell suspensions were centrifuged at 1200 rpm for 10 minutes, the wells were aspirated, washed with a Tween 80 (0-05%) saline (0 85%) wash solution, and filled with ethylene glycol for five minutes to fix antigen to the plastic wells.…”
Section: Assessment Of Monoclonal Antibody Specificitymentioning
confidence: 99%
“…Several investigators have described the presence of bacterial structures in various samples from patients with sarcoidosis (47)(48)(49)(50)(51)(52). Initially, these structures were characterized as cell wall-deficient (CWD) bacteria (50,51) and later as acid-fast bacilli (AFB).…”
Section: Histology and Bacteriologymentioning
confidence: 99%